(3eNJUQ GdbGfhfs - (3eLghds
(3ChdgG (B:s
(3GeQJfi HEfTGA cJGH jLeY CbhGd GdWH eNJUQI heLQOI ef GdEWfGH hGdEWGdI GdeedI hgPG GdcJGH YTQ ebGdGJ (B: (3GdChdi ai Ndb GdEfSGf hJQcjH GdLSO hJb(B4(3Sje GdWH heYQaI GdfHV s
(3BNQgG (B:s
(3aGdMei Qbb, hEPG JecfJ gPg GdMei , YTQ YdGLgG hJYPQ RhGdgGJeJ GdebGdI GdYGTQg hgj BNQ GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdWHs